Pengaruh Islamic Branding dan Streamer Product Knowledge terhadap Minat Beli Kosmetik Halal Dimediasi Kepercayaan - Dwi Nabilah Nur Utari; Fikriyah, Khusnul (Indonesian Journal of Islamic Economics and Business, 2025)
This study aims to analyze the influence of Islamic branding and streamer product knowledge on the purchase intention of halal cosmetics through live shopping, with trust as a mediating variable among Muslim consumers in East Java. This research uses a quantitative method, with primary data collected through online questionnaire distribution. The sampling technique employed was purposive sampling, involving 135 respondents. Data analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS) with the SmartPLS4 software. The results show that (1) Islamic branding does not influence purchase intention, (2) streamer product knowledge positively influences purchase intention, (3) Islamic branding does not influence trust, (4) streamer product knowledge positively influences trust, and (5) Islamic branding and streamer product knowledge do not affect the purchase intention of halal cosmetics through trust as a mediating variable. These findings indicate that, in the context of live shopping, a streamer's product knowledge plays a crucial role in building consumer trust and encouraging purchase intention, whereas Islamic branding does not directly influence consumer purchasing behavior. This research provides valuable insights for the development of marketing strategies for halal cosmetic products, particularly in leveraging live shopping platforms to reach Muslim consumers.